Criminological Analysis of Banking Crimes in Makassar City - Nur Fadhilah Mappaselleng; Siddik, Andar (Alauddin Law Development Journal (ALDEV), 2024)
This research aims to analyze the factors causing banking crime in Makassar City and the prevention efforts of the South Sulawesi Regional Police. Data was gathered from direct interviews with 20 respondents, including 10 investigators, 5 bank employees, and 5 victims of banking crime. The findings indicate that supervision, technological, economic, and opportunity factors are the main causes of banking crime in Makassar City. The police's preventive measures include legal counseling, patrols, routine supervision, community policing, and investigations. The research recommends revising the Banking Law to adapt to the banking industry's changes and challenges in the digital era. Additionally, improving police resources' quality and training in knowledge, skills, and integrity are crucial for future action.